2011
DOI: 10.1177/1049909110397926
|View full text |Cite
|
Sign up to set email alerts
|

When to Say “Yes” and When to Say “No”

Abstract: A total of 79 hospice palliative care volunteers from 2 community-based hospice programs responded to a 27-item Boundary Issues Questionnaire that was specifically developed for this study. Volunteers were asked to indicate whether or not they considered each item (eg, "Lend personal belongings to a patient or family," "Agree to be a patient's power of attorney," "Attend/go into a patient's medical appointment") to be something they should not do and to indicate whether or not they have ever done it. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…In community hospice programs, volunteers play a vital but circumscribed role focused primarily on providing companionship to patients and respite to family caregivers (Berry & Planalp, 2009, Claxton-Oldfield, Gibbon, & Schmidt-Chamberlain, 2011). In the prison peer-care volunteer model described here, in contrast, volunteers provide the majority of hospice patient care and psychosocial support on a one-to-one basis, including symptom assessment and non-pharmacological management, assistance with activities of daily living such as bathing, toileting, assistance with eating or feeding, skin care, and mobility, companionship, and spiritual support if this is what the patient requests.…”
Section: Discussion: Caring To Learnmentioning
confidence: 99%
“…In community hospice programs, volunteers play a vital but circumscribed role focused primarily on providing companionship to patients and respite to family caregivers (Berry & Planalp, 2009, Claxton-Oldfield, Gibbon, & Schmidt-Chamberlain, 2011). In the prison peer-care volunteer model described here, in contrast, volunteers provide the majority of hospice patient care and psychosocial support on a one-to-one basis, including symptom assessment and non-pharmacological management, assistance with activities of daily living such as bathing, toileting, assistance with eating or feeding, skin care, and mobility, companionship, and spiritual support if this is what the patient requests.…”
Section: Discussion: Caring To Learnmentioning
confidence: 99%
“…Previous studies have also reported that volunteering generally increases with educational attainment whereby those with higher levels of formal education are more likely to volunteer than others and may contribute more hours in volunteering (Hall et al, 2009;Claxton-Oldfield et al, 2011;Wilson & Newman, 2011). Their findings advanced the idea who were employed were more likely to volunteer as compared to those who were unemployed.…”
Section: Volunteering Work Across Gender Ethnicity and Education Levelmentioning
confidence: 99%
“…This study further supports the studies done by Zweigenhattm et al, (1996) and Lindenmeir (2008), which found that women are more likely to engage in voluntary work and are more dependable compared to their male counterparts. On the other hand, it also found that those who were married and having partners, compared to single individuals, were likely to feel rushed and have lesser time to spare for other work such as volunteerism (Warburton and Crosier, 2001;Claxton-Oldfield et al, 2011).…”
Section: Volunteering Work Across Gender Ethnicity and Education Levelmentioning
confidence: 99%
“…De frivillige beskrives som betydningsfulde mellemled mellem professionelle og den hjaelp-traengende og dennes pårørende, saerligt når frivilligheden udføres hos borgere i eget hjem (52,55). Studier viser, at frivilliges centrale rolle også betyder udfordringer knyttet til afgraensning mellem frivilliges og professionelles opgaver (52,56,57). Internationale studier har da også vaeret optaget af frivilliges oplaering til det palliative felt ( [58][59][60][61], hvor krav og omfang kan variere betydeligt på tvaers af lande (62).…”
Section: Forskning Om Frivilligt Arbejde I Palliationunclassified
“…Der var en eller flere ansatte aktivitetskoordinatorer, hvis hovedopgave var den daglige kontakt til ca. [50][51][52][53][54][55][56][57][58][59][60]…”
Section: Rekruttering Af Kommuner Og Plejehjemunclassified